What is kangaroo mother care? Systematic review of the literature - Grace J Chan; Bina Valsangkar; Sandhya Kajeepeta; Ellen O Boundy; Stephen Wall (Edinburgh University Global Health Society, 2016)
Kangaroo mother care (KMC), often defined as skin-to-skin contact between a mother and her newborn, frequent or exclusive breastfeeding, and early discharge from the hospital has been effective in reducing the risk of mortality among preterm and low birth weight infants. Research studies and program implementation of KMC have used various definitions.